2015
DOI: 10.1002/2014jf003351
|View full text |Cite
|
Sign up to set email alerts
|

Determination of warm, sensitive permafrost areas in near‐vertical rockwalls and evaluation of distributed models by electrical resistivity tomography

Abstract: Alpine rockwalls with warm permafrost (near 0°C) are the most active rockfall detachment zones in the Mont Blanc massif (MBM, French Alps) with more than 380 recent events. Near-vertical rockwall permafrost is spatially controlled by variations in rock fractures, snow cover, and microtopography. A reliable method to validate the distribution of permafrost in critical and unstable areas does not yet exist. We present seven electrical resistivity tomography (ERT) surveys measured on five near-vertical rockwalls … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 51 publications
0
36
0
Order By: Relevance
“…Böhlert et al (2008) and Gallach et al (2018) suggest that the morphology of present-day rockwalls mainly results from a juxtaposition of rockfall scars of variable ages. (Magnin et al, 2015), and rockfall events are mainly triggered by permafrost warming (Gruber and Haeberli, 2007;Deline et al, 2012). Further, 10 Be ages of between less than 0.5 and 60 ka have been measured on the rockwalls (Böhlert et al, 2008;Gallach et al, 2018).…”
Section: Sidewall Erosion Processes In the Mont Blanc Massifmentioning
confidence: 99%
“…Böhlert et al (2008) and Gallach et al (2018) suggest that the morphology of present-day rockwalls mainly results from a juxtaposition of rockfall scars of variable ages. (Magnin et al, 2015), and rockfall events are mainly triggered by permafrost warming (Gruber and Haeberli, 2007;Deline et al, 2012). Further, 10 Be ages of between less than 0.5 and 60 ka have been measured on the rockwalls (Böhlert et al, 2008;Gallach et al, 2018).…”
Section: Sidewall Erosion Processes In the Mont Blanc Massifmentioning
confidence: 99%
“…It recorded the rock temperature at depths of 3, 10, 30 and 55 cm until January 2013. The 2012 mean annual rock surface temperature (MARST) at a depth of 3 cm was −1.4 • C. In 2012 and 2013, electrical resistivity tomography (ERT) soundings were conducted along the NW face of the GM and four other sites of the massif (Magnin et al, 2015d). The potential of ERT for qualitative evaluation of 2-D permafrost models has been demonstrated by , as it covers a much wider and deeper rock wall portion than borehole.…”
Section: Grands Montets and Ert Datamentioning
confidence: 99%
“…The potential of ERT for qualitative evaluation of 2-D permafrost models has been demonstrated by , as it covers a much wider and deeper rock wall portion than borehole. This makes ERT a potentially better approach with which to evaluate distributed models of rock wall permafrost because it has the capacity to represent the spatial variability of rock wall permafrost (Magnin et al, 2015d). Conversely, direct temperature measurements allow for quantitative evaluation, but have the disadvantage of being only representative for the measurement point.…”
Section: Grands Montets and Ert Datamentioning
confidence: 99%
“…The difference is caused by different amount of gravitational type of water in the topsoil. It has been previously shown that electrical resistivity is decreasing with higher amount of gravitational type of water in soil pores (Samouëlian et al 2005, Pozdnyakov 2008, Magnin et al 2015. The depths of the active layer-permafrost boundary lies on the depth 80-90 cm and are shown in Fig.…”
Section: Resultsmentioning
confidence: 88%